ANALISIS CAMPUR KODE DAN ALIH KODE PADA PERCAKAPAN GURU DAN SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IX SMP NEGERI 3 SATU ATAP ARAMO - Laia, Sayangi (Universitas Nias Raya, 2023)
This research is motivated by the emergence of language mixing and switching in teacher and student conversations. The objectives of this research are (1) To describe the code mixing used in teacher and student conversations in Indonesian language learning (2) To describe the code switching used in teacher and student conversations in Indonesian language learning (3) To analyze the factors that causes code mixing and code switching in teacher and student conversations in Indonesian language learning. The research method used is a data analysis method where there are three series of activities, namely (1) reduction (2) data presentation (3) drawing conclusions (verification). Based on the results of the analysis, data presentation and research findings regarding the use of code switching and code mixing in Indonesian language learning in class IX of SMP Negeri 3 Satu Roof Aramö T.P. 2022/2023, researchers found that there were 2 uses of code switching and 3 uses of code mixing. Indonesian language learning in class IX of SMP Negeri 3 One Roof Aramö T.P. 2022/2023. Based on the results of the research above, the researcher concluded that Indonesian language learning in class IX of SMP Negeri 3 Satu Roof Aramö T.P. 2022/2023 uses code switching and code mixing because the writers adapt to the interlocutor, to clarify a certain meaning and are only temporary. Based on the conclusions above, it is hoped that we can provide suggestions to the community and researchers, (1) teachers and students should try to expand the city so that they do not get used to using code switching, (2) teachers/lecturers should provide education about the importance of using language and provide explanations. to the public about code switching and code mixing.